Pediatric Inflammatory Bowel Disease in Asia: Epidemiology and natural history - James Guoxian Huang; Marion M. Aw (Pediatrics and Neonatology)
Pediatric inflammatory bowel disease (PIBD) in Asia, once considered a rare entity, has seen a sharp increase in incidence over the preceding decade. However, there is a paucity of epidemiological data on PIBD in Asia, and the true disease burden is difficult to estimate due to the lack of national disease registries, prospective databases and the fact that much of existing published data are limited to single-center experiences. This sets the stage for examining recent published data on epidemiological trends and its natural history. Hence, we reviewed the relevant published literature on PIBD in order to summarize the epidemiological data in the Asian populations and compare it with the data available from the other population including Western population. Our review demonstrates that the rapid surge in PIBD incidence across Asian centers lies in contrast to the plateauing albeit high incidence rates in larger established Western cohorts. Important epidemiological trends observed across emerging Asian literature are the higher rates of perianal involvement at disease onset amongst pediatric Crohn's disease (CD) patients, a higher proportion of early-onset disease and the over-representation of the Indian ethnicity in multi-ethnic cohorts. A number of issues currently limit a robust comparison and hence the way forward would be to advocate the recognition of PIBD as an increasingly important public health problem with the need to establish robust disease registries.